2010
DOI: 10.1111/j.1651-2227.2009.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐label and off‐label use of respiratory drugs in the Italian paediatric population

Abstract: In Italy, many respiratory drugs are approved for the treatment of paediatric respiratory diseases, but a remarkable percentage of their prescriptions is off-label. This pharmaco-utilization study demonstrates that there is a need to perform clinical studies aimed at increasing the current knowledge on marketed paediatric drugs, and to revise and re-label the existing regulatory documents to reduce their off-label uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
2
9

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 24 publications
1
30
2
9
Order By: Relevance
“…In the case of the respiratory system, anticholinergic and β 2 adrenoreceptors agonists are drugs to treat associated diseases, and our findings show that off-label and/or unlicenced prescriptions included items such as ipratropium bromide [19,21,31,42] and salbutamol [19,21,23,25,42]. Some authors [58][59][60] reported that drugs used for the respiratory system were widely administered and that a high percentage of such drugs were prescribed off-label, accounting for 20 % of all prescriptions.…”
Section: 5mentioning
confidence: 62%
“…In the case of the respiratory system, anticholinergic and β 2 adrenoreceptors agonists are drugs to treat associated diseases, and our findings show that off-label and/or unlicenced prescriptions included items such as ipratropium bromide [19,21,31,42] and salbutamol [19,21,23,25,42]. Some authors [58][59][60] reported that drugs used for the respiratory system were widely administered and that a high percentage of such drugs were prescribed off-label, accounting for 20 % of all prescriptions.…”
Section: 5mentioning
confidence: 62%
“…Respiratory drugs are frequently prescribed to paediatric patients for a wide range of airway diseases but most of these drugs are only approved for asthma and COPD from a particular age onwards [1], [2]. In young children, diagnosing asthma is difficult due to general limitations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, respiratory drugs are frequently used for symptomatic improvement of airway diseases (e.g. acute respiratory infections) or are prescribed as a diagnostic instrument to confirm a diagnosis of asthma [1], [2]. All these reasons contribute to a high fraction of children receiving respiratory medication as off-label treatment [1], [2], a factor which has been reported as a risk for adverse drug reactions [4][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on the safety and efficacy of these drugs with children is still lacking [8]. Baiardi et al [9] reported that a significant percentage of the medicines used for pediatric respiratory diseases in Italy were prescribed offlabel. The evidence available for the use of medicines in children with respiratory diseases has been reviewed by the European Respiratory Society task force which highlighted the gaps and research priorities in this area [10].…”
Section: Introductionmentioning
confidence: 99%